Gradual Payment Scheme Investment Fee for Power Plant Operation and Maintenance (O&M) Services - Aryata I Made; Marendra I Gede (Enrichment : Journal of Management, 2022)
PT Pebangkitan Jawa-Bali (PJB) as a subsidiary of PT PLN (Persero) (PLN) has business fields which include: Electricity Generation, Electrical Building Construction, Installation of electrical equipment; Maintenance and/or operation of electrical equipment; and Trading and/or supporting business activities in the context of optimizing the utilization of the Company's resources. PJB has experience in operating and maintaining PLN power plants (O&M) with a total capacity of 6,246 MW. There are 2 schemes in power plant O&M services, namely as asset operator and asset manager. By using the asset manager scheme, PLN can make investment payments in stages with an agreed IRR target of 7%. In this study, analyze the gradual payment options which are divided into 3 options to compare the current gradual payment scheme with the proportion of payments evenly distributed each year. From the analysis results, it is known that gradual payment changes through option-1, option-2 and option-3 can reduce the total return on investment costs that will be received by PLN while maintaining the IRR target of 7% and a Positive NPV. Of the three options, option-3 is able to reduce the cost of return on investment by Rp. 9,970 million with an IRR of 7.38% and an NPV of Rp. 8,660 million. And through option-3, the investment return burden that must be paid by PLN at the end of the period is only 32% of the total investment return for 5 years